Estudio y diseño del sistema de alcantarillado sanitario - pluvial y agua potable, para la lotización ampliación de la ciudadela 8 de septiembre de la ciudad de Huaquillas, provincia de El Oro. - Ruilova Dávila, Juan Orlando (2015)
The absence of a network of drinking water distribution system, sanitary and storm sewer for Allotment Expansion citadel September 8 City Huaquillas, threatens the health of its residents, and allows the spread of diseases, and consequently pollutes the environment. Objective is planned to provide this health service sector, stormwater and sewage water to solve the problems of poor health, and thus improve their standard of living and development. For this research mode literature review, documentary, online consultations, with the support of field research on the level of exploratory, descriptive and practical, in contact with the sector was used. The results of socioeconomic surveys, topography, soil survey, gauging, physical and chemical analysis of water, were interpreted, calculated and used to design systems AASS, according INEN standards Level 3 with a length of 2168m with tub. Profiled PVC Ф 200mm, 38pozos review, AALL of 2250m with tub. Profiled PVC Ф 250 to 750mm, 38 AAPP network of 3912m with tub wells review, a discharge structure, and. PVC E / C 1.2MPa 160mm Ф 32 to 11 hydrants, elevated tank of 70m ^ 3. In conclusion, this project is viable as it was reviewed by technical specialists in this field, and can continue with the construction stage for any company that has sufficient financial resources.